Dene traditional knowledge about caribou cycles in the Northwest Territories - Beaulieu, Danny (Rangifer, 2012)
This paper is about what I have learned about the caribou cycle over the past one hundred and ten years or so, talking to Denesųłıné elders in Fort Resolution, Łutselk’e, and Yellowknife. Mostly I’ve learned from my grandmother, my grandparents, and my parents.